Nursing Effect and Prognosis Analysis of Self-Management Education Model Based on Protective Motivation Theory on Patients with Hematological Tumor after PICC Catheterization. (13th May 2022) - Jiang, Lili; Yang, Xiuying; Xi, Lu; Zhang, Chaolang
Abstract : Objective . To analyze the nursing effect and prognostic value of self-management education model based on protective motivation theory on patients with hematological malignancies (HM) after peripheral venous catheterization (PICC). Methods . A total of 90 patients with HMs treated with PICC catheterization in our hospital from October 2019 to October 2021 were included in the study. The patients were randomly assigned into experimental group (n = 45 ) and control group (n = 45 ). On the basis of the control group, the experimental group implemented the self-management education model based on the theory of protective motivation, and the control group implemented routine nursing health education measures. The self-nursing ability scale (ESCA), Hamilton anxiety scale (HAMA), the average cost of PICC catheter maintenance, the incidence of PICC-related complications, and the score of Newcastle nursing satisfaction scale (NSNS) were observed 1 month before and after nursing. Results . After one month of nursing, there was no significant difference in ESCA self-concept (p > 0.05 ). After one month of nursing, the scores of self-care responsibility, self-nursing skills, and health knowledge in the experimental group were significantly higher compared to those before nursing (p < 0.05 ) and higher compared to those in the control group (p < 0.05 ). After one month of nursing, the score of HAMA scale was significantly lower compared to that before nursing (p < 0.05 ), and the score of HAMA scale in the experimental group was lower compared to the control group (p < 0.05 ). After one month of nursing, the average cost of PICC pipeline maintenance in the test group was lower than that in the control group (p < 0.05 ). One month after nursing, the incidence of PICC-related complications in the experimental group was lower than that in the control group (p < 0.05 ). One month after nursing, the score of NSNS scale was significantly higher than that before nursing (p < 0.05 ). After one month of nursing, the score of NSNS scale in the experimental group was higher than that in the control group. Conclusion . The self-management education model based on protective motivation theory is effective in nursing patients with peripheral venous catheterization and PICC catheterization of HMs. It is more beneficial to promote patients' self-nursing management ability, reduce anxiety, reduce the average cost of PICC pipeline maintenance, reduce the incidence of PICC-related complications, and enhance nursing satisfaction.